Figurative Language Methods as Strategies of Sociopolitical Criticism in Jan Svankmajer's Films - Ahmad Khoshniat (ITB Journal Publisher, LPPM ITB, 2020)
The aim of this study was to evaluate the sociopolitical critique strategies used by Jan Svankmajer in his films. Figurative language in literature means speaking in an indirect way by using words with a meaning other than their literal meaning. An important part of this study was aimed at establishing the parallels between various modes of figurative language and the films of Svankmajer, which can both be used to indirectly criticize contemporary sociopolitical issues. The research method of this study was based on finding the equivalents of various figurative language modes in filmmaking techniques used by Svankmajer. Thus, figurative language modes were identified using a literature review. The structure of Svankmajer's filmmaking techniques was analyzed and set side by side with figurative language modes by an analytical-comparative approach.